2022
DOI: 10.48550/arxiv.2210.01417
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The impacts of solar wind on the Martian upper atmosphere

Abstract: Since the first in-situ measurements of the altitude profile of upper atmospheric density and composition were carried out by the Viking lander missions in 1976, similar data are continuously gathered by MAVEN and MOM spacecraft orbiting Mars since their launch in September 2014 with mass spectrometers and other related payloads. Using near-simultaneous observations by the two orbiters, it is seen that both data sets indicate significant day-to-day variations of Argon (Ar) density profiles in the thermosphere-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…In addition to the in situ and remote measurements, a new Mars Global Ionosphere-Thermosphere Model (MGITM) is developed to accurately describe the features of the compositional and thermal structure of the Martian thermosphere (Bougher et al 2015). Observations and simulations have revealed that the structure and circulation of this region were driven both by energy and momentum fluxes from the lower atmosphere and by solar X-ray/Extreme Ultraviolet (EUV) radiation, solar energetic particle as well as solar wind influx from above (e.g., Bougher 1995;Krasnopolsky 2002;Bougher et al 2015;Nagaraja & Chakravarty 2022;Wu et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the in situ and remote measurements, a new Mars Global Ionosphere-Thermosphere Model (MGITM) is developed to accurately describe the features of the compositional and thermal structure of the Martian thermosphere (Bougher et al 2015). Observations and simulations have revealed that the structure and circulation of this region were driven both by energy and momentum fluxes from the lower atmosphere and by solar X-ray/Extreme Ultraviolet (EUV) radiation, solar energetic particle as well as solar wind influx from above (e.g., Bougher 1995;Krasnopolsky 2002;Bougher et al 2015;Nagaraja & Chakravarty 2022;Wu et al 2022).…”
Section: Introductionmentioning
confidence: 99%